1997
DOI: 10.1111/j.1399-0039.1997.tb02890.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐A typing: comparison between serology, the amplification refractory mutation system with polymerasee chain reaction and sequencing

Abstract: In this study we typed HLA-A polymorphisms by a new sequence-based typing (SBT) method, which involved one PCR reaction and four sequencing reactions covering exon 2 and exon 3. This method allowed complete identification of all known HLA-A alleles and revealed the presence of a new allele, named HLA-A*2608. We also introduced sequencing of exon 4 for some samples in order to discriminate the allelic pairs that are identical in exon 2 and 3, thus improving SBT resolution. Finally, we compared the results obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Amplification and sequencing protocols for typing by PCR-SBT of class I loci were described in previous reports. [11][12][13] Briefly, for HLA-B and -C loci, only one locus-specific amplification of exons 2 and 3 was performed using primers located in introns 1 and 3, near the polymorphic exons. For HLA-A locus, the amplification spanned exon 1 to exon 4.…”
Section: Hla High-resolution Typingmentioning
confidence: 99%
See 1 more Smart Citation
“…Amplification and sequencing protocols for typing by PCR-SBT of class I loci were described in previous reports. [11][12][13] Briefly, for HLA-B and -C loci, only one locus-specific amplification of exons 2 and 3 was performed using primers located in introns 1 and 3, near the polymorphic exons. For HLA-A locus, the amplification spanned exon 1 to exon 4.…”
Section: Hla High-resolution Typingmentioning
confidence: 99%
“…Additional sequencing of exons 1 and 4 led to complete resolution of all HLA-A polymorphisms. 11 The ambiguous heterozygous patterns were solved through allele-specific amplification followed by direct sequencing of the product. An analogous approach was used for the DR and DQ loci typed according to previously described techniques.…”
Section: Hla High-resolution Typingmentioning
confidence: 99%
“…DNA-based HLA typing revealed that HLA-A24 consists of at least 7 sub-types and that HLA-A24 sub-type, HLA-A*2402 is in the majority of samples more than 95% in the various populations (Pera et al, 1997). An analysis of 553 unrelated Japanese revealed that the antigen frequency of HLA-A24 is 61.2% and that 99.3% of the HLA-A24 sub-type is HLA-A*2402 (Date et al, 1996).…”
Section: Recognition Of Scchn Cell Lines Expressing Both Hla-a24 Molementioning
confidence: 98%
“…Specific PCR amplification including exons 2 and 3 of the HLA-A locus (accession number AJ278305.1) was obtained using two locus-specific primers, located in intron 1 (A intr1Fnew) and in intron 3 (A intr3Rnew) [Pera et al, 1997]. PCR reactions were performed by a ''hot start'' method using an ''upper mix'' consisting of 10 ml 5 Â Buffer A, 5 ml 10 mM dNTPs (2.5 mM of each dNTP), 0.3 ml AmpliTaq PE, 1 ml Primer Forward (10 pmol/ml), and a ''lower mix'' composed of 5 ml dimethyl sulfoxide (DMSO), 1 ml Primer Reverse (10 pmol/ml), 250 ng of genomic DNA, and ddH2O up to 50ml.…”
Section: Dna Ampli¢cationmentioning
confidence: 99%